The development concept of digital advertising preference - Alamsyah, Doni Purnama; Aryanto, Rudy; Mulyani, Mulyani; Kurnianingrum, D; Indriana, Indriana; Othman, Norfaridatul Akmaliah; Hasan, Hazmilah (2023)
Technology continues to be improved and developed to support organizational performance. In consumer behavior and advertising science, technology is used to support education in advertising. Based on the phenomenon of advertising, this study aims to investigate the concept of digital advertising preference. The research was conducted through a literature review from several research experts and was studied descriptively to find the concept of digital advertising preference. The research findings show that digital advertising preference can be built through the concept of search engine advertising, interactive advertising, opt-in advertising, social media networks, and mobile advertising. Also, it is known that there is a relationship between digital advertising preference and consumer behavior through brand awareness.